ADAM17-triggered TNF signalling protects the ageing Drosophila retina from lipid droplet-mediated degeneration. - Muliyil, S.; Levet, C.; Düsterhöft, S.; Dulloo, I.; Cowley, S.A.; Freeman, M. (The EMBO Journal, 2020)
Animals have evolved multiple mechanisms to protect themselves from the cumulative effects of age-related cellular damage. Here, we reveal an unexpected link between the TNF (tumour necrosis factor) inflammatory pathway, triggered by the metalloprotease ADAM17/TACE, and a lipid droplet (LD)-mediated mechanism of protecting retinal cells from age-related degeneration. Loss of ADAM17, TNF and the TNF receptor Grindelwald in pigmented glial cells of the Drosophila retina leads to age-related degeneration of both glia and neurons, preceded by an abnormal accumulation of glial LDs. We show that the glial LDs initially buffer the cells against damage caused by glial and neuronally generated reactive oxygen species (ROS), but that in later life the LDs dissipate, leading to the release of toxic peroxidated lipids. Finally, we demonstrate the existence of a conserved pathway in human iPS-derived microglia-like cells, which are central players in neurodegeneration. Overall, we have discovered a pathway mediated by TNF signalling acting not as a trigger of inflammation, but as a cytoprotective factor in the retina.